Studies in the history of the English language VIII boundaries and boundary-crossings in the history of English - Grund, Peter 1975-; Hartman, Megan E. (Topics in English linguistics, 2020)
This volume collects essays that approach notions of creating, maintaining, and crossing boundaries in the history of the English language. The concept of boundaries is variously defined within linguistics depending on the theoretical framework, from formal and theoretical perspectives to specific fields and more empirical, physical, and perceptual angles. The contributions to this volume do not take one particular theoretical or methodological approach but, instead, explore how examining various types of boundaries-linguistic, conceptual, analytical, generic, physical-helps us illuminate and account for historical use, variation, and change in English. In their exploration of various topics in the history of English, contributions ask a range of questions: what does it mean to set up boundaries between time periods? When do language varieties have distinct boundaries and when do they overlap? Where do language users draw up clausal, constructional, semantic, phonetic/phonological boundaries? Thus, the chapters explore not only how boundaries illustrate synchronic and diachronic features in the history of the English language but also what we can discover by questioning perceived or actual boundaries